2022
DOI: 10.1039/d2qo00056c
|View full text |Cite
|
Sign up to set email alerts
|

Water facilitated photolysis of perfluoroalkyl iodidesviahalogen bonding

Abstract: Sigma (σ)-hole effect of perfluoroalkyl iodide, an interaction between the σ* orbitals of C-I bond and a Lewis base, has proven efficient for the generation of perfluoroalkyl radicals via single...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In this context, a water facilitated photolysis of perfluoroalkyl iodides via halogen bonding has been recently reported. [33] To demonstrate the scalability of the methodology herein reported, the fluoroalkylation of DB24 C8 was carried out on a gram-scale affording 65 % (0,98 g) isolated yield of product 16 (see SI for details). The utility of the methodology is further highlighted by the post-synthetic fluoroalkylation of a mechanically interlocked molecule (MIM) [34] such as [2]rotaxane 20.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, a water facilitated photolysis of perfluoroalkyl iodides via halogen bonding has been recently reported. [33] To demonstrate the scalability of the methodology herein reported, the fluoroalkylation of DB24 C8 was carried out on a gram-scale affording 65 % (0,98 g) isolated yield of product 16 (see SI for details). The utility of the methodology is further highlighted by the post-synthetic fluoroalkylation of a mechanically interlocked molecule (MIM) [34] such as [2]rotaxane 20.…”
Section: Resultsmentioning
confidence: 99%
“…122 It has been confirmed that water facilitates the iodoperfluoroalkylation reaction of alkenes and alkynes via the formation of an EDA complex between water and the iodoperfluoroalkane, which upon excitation by visible light delivers the fluoroalkyl radical efficiently. 40 Very recently, Wang, Chen, Beller, and colleagues 44 disclosed the activation of R F −I bonds in the presence of KOH to generate R F radicals, which subsequently perform an ATRA reaction on alkenes and alkynes. The scope of the reaction is illustrated in Scheme 33A.…”
Section: Iodoperfluoroalkylations: Syntheses Of Iodoperfluoroalkylate...mentioning
confidence: 99%
“…The iodoperfluoroalkylation reaction has also been performed in water by direct irradiation of perfluoroalkyl iodides in the presence of alkenes and alkynes, or more recently by Rose Bengal photocatalysis . It has been confirmed that water facilitates the iodoperfluoroalkylation reaction of alkenes and alkynes via the formation of an EDA complex between water and the iodoperfluoroalkane, which upon excitation by visible light delivers the fluoroalkyl radical efficiently …”
Section: Perfluoroalkyl Radical Additions Followed By Group Transfer ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, DFT and TD-DFT calculations revealed that (i) the formation of the dppm– 2a complex ( I ) is enthalpically favored by −3.6 kcal/mol and is endergonic by only 6.6 kcal/mol (Figure H) and (ii) different conformers of complex I and their Na 2 CO 3 adducts have absorptions extending into the visible light region (Figures S14–S16). , These conformers and adducts are higher in energy and may exist at concentrations outside the detection limit of the UV–Vis spectrometer.…”
mentioning
confidence: 99%